Bullous skin signs and laboratory surgical indicators can quickly and effectively differentiate necrotizing fasciitis from cellulitis. (March 2023) - Tsai, Yao-Hung; Chen, Hung-Yen; Huang, Tsung-Yu; Chen, Jiun-Liang; Hsiao, Cheng-Ting; Huang, Kuo-Chin
Highlights: Necrotizing fasciitis (NF) and cellulitis are difficult to differentiate at initial onset. Hemorrhagic bullae presentation is significantly associated with NF and mortality. Five diagnostic indicators were identified for differentiating NF from cellulitis. Abstract: Objectives: The purpose of this prospective study was to investigate the different microorganisms associated with mortality, to evaluate the bullous skin sign, and to identify the positive predictive factors for differentiating necrotizing fasciitis (NF) from cellulitis on initial onset at the emergency department. Methods: This prospective study was conducted in 145 consecutive patients with NF and 159 patients with cellulitis. Age, sex, comorbidities, infection site, microbiological results, condition of skin lesions, laboratory findings, vital signs, and clinical outcomes were compared between the two groups at the time of admission to the emergency room. Results: A total of 15 patients in the NF group and two patients in the cellulitis group died, resulting in a mortality rate of 10.3% and 1.3%, respectively. The NF group had a significantly higher incidence of white blood cell counts, band form neutrophil, and C-reactive protein than the patients in the cellulitis group. Hemorrhagic bullae presentation appeared to have significantly associated with NF and death. Conclusion: The following diagnostic indicators can be effectively used to differentiate NF from cellulitis at the initial onset: presence of hemorrhagic bullae, white blood cell counts >11, 000 cells/mm 3, band forms >0%, C-reactive protein >100 mg/l, and systolic blood pressure ≤90 mm Hg at the time of consultation.